2014
DOI: 10.5152/tjg.2014.4967
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to diagnose infectious oesophagitis without seeing the causative organism? A histopathological study

Abstract: Background/Aims: We investigated the utility of using histological changes to diagnose infectious oesophagitis when causative organisms cannot be seen. Materials and Methods: Sixty-seven endoscopic biopsy specimens (51 Candida, 9 herpes simplex virus, 4 tuberculosis, and 3 cytomegalovirus oesophagitis) collected from 2000-2010 that matched the investigative criteria were included in the study. Cases were re-evaluated for histological changes observed in oesophagitis, and the findings were statistically compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
11
0
1
Order By: Relevance
“…In patients with normal immune function, cytomegalovirus esophagitis mainly presents with chest pain, swallowing pain, hematemesis, and melena, as well as patients with weight loss, difficulty in swallowing, etc. Cytomegalovirus esophagitis in immunocompetent patients and immunodeficient patients showed similar clinical symptoms, which is consistent with previous reports [10]. Endoscopic manifestations of esophageal mucosal erosion, ulcers, erosions and ulcers often occur in the lower esophagus, but also occur in the upper esophagus.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with normal immune function, cytomegalovirus esophagitis mainly presents with chest pain, swallowing pain, hematemesis, and melena, as well as patients with weight loss, difficulty in swallowing, etc. Cytomegalovirus esophagitis in immunocompetent patients and immunodeficient patients showed similar clinical symptoms, which is consistent with previous reports [10]. Endoscopic manifestations of esophageal mucosal erosion, ulcers, erosions and ulcers often occur in the lower esophagus, but also occur in the upper esophagus.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, desquamated tissue fragments and detached yeast may be lost as a result of prior cytological brushings or during tissue processing 11,31 . In these situations, other histological changes, such as reactive epithelial changes or intraepithelial neutrophils, may be helpful diagnostic clues 2,30,32 . However, approximately one‐quarter of the patients in our study had oesophageal biopsies that showed fungal invasion of the squamous epithelium unaccompanied by neutrophil‐rich inflammation.…”
Section: Discussionmentioning
confidence: 90%
“…Although these data suggest that asymptomatic Candida oesophagitis is of little clinical significance in some patients, criteria for distinguishing patients who require therapy from those who do not remain unclear; asymptomatic patients can certainly have endoscopically apparent oesophagitis with exudates and fungi in oesophageal biopsy samples. Oesophageal biopsies with Candida are usually described as containing budding yeast and/or pseudohyphae, variably present neutrophilic and/or lymphocytic infiltrates, superficial exudates of desquamated epithelial cells, and reactive squamous epithelial changes that may mimic other types of oesophagitis 5,19,30 . Historically, many pathologists have required the presence of pseudohyphae and/or fungal invasion of intact epithelium to establish a diagnosis of clinically significant infection, but our data show that patients with clinically significant infections often lack these features.…”
Section: Discussionmentioning
confidence: 99%
“…13 The role of lymphocytes in relation to neutrophils and eosinophils has also been studied in the context of infectious esophagitis. 14 A few lymphocytes are normally present in the esophageal squamous mucosa, however, a normal number is not defined. An early study by 16 Intraepithelial lymphocytes in the esophagus have also been reported in association with inflammatory bowel disease, 17,18 although an association specifically between lymphocytic esophagitis and inflammatory bowel disease has not been a universal finding.…”
Section: Discussionmentioning
confidence: 99%